2006
DOI: 10.1260/026361706778529164
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Pb(II) Ions from Aqueous Solution Using a Coir-Based Product (Puresorbe)

Abstract: ABSTRACT:The effectiveness of Pb(II) ion removal from wastewater by adsorption methods has made this an ideal alternative to other expensive treatment options. This paper describes an investigation using a coir-based adsorbent (Puresorbe) for the removal of Pb(II) ions from aqueous solution. The adsorption of Pb(II) ions was studied varying parameters such as the agitation time, the metal ion concentration, the adsorbent dose, the temperature and the pH of the aqueous solution. The experimental isotherm data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As the pH increased the net surface change has become negative thus the percent removal decreased. The pH ZPC of puresorbe was found to be 5.5 [11], this indicates that at pH lower than 5.5, the surface of puresorbe is positively charged and chromium is mainly present as HCrO 4 − at pH 2, at which maximum removal was observed at equilibrium condition for puresorbe. Similar observation was recorded by Elliot and Weng for Cr(VI) onto fly ashes [12].…”
Section: Thermodynamic Studiesmentioning
confidence: 87%
“…As the pH increased the net surface change has become negative thus the percent removal decreased. The pH ZPC of puresorbe was found to be 5.5 [11], this indicates that at pH lower than 5.5, the surface of puresorbe is positively charged and chromium is mainly present as HCrO 4 − at pH 2, at which maximum removal was observed at equilibrium condition for puresorbe. Similar observation was recorded by Elliot and Weng for Cr(VI) onto fly ashes [12].…”
Section: Thermodynamic Studiesmentioning
confidence: 87%
“…These studies were performed at pH 4 where the solution pH was adjusted by adding HNO 3 or NaOH and mixing with a glass stirrer. Note that this solution pH was selected to avoid the precipitation of Cd(II) and Pb(II) ions as hydroxides (i.e., Cd(OH) 2 and Pb(OH) 2 at pH > 5 and 6, respectively) [48, 49] and to prevent the zeolite dealumination [31, 50]. Other studies have also reported that a maximum adsorption capacity of Pb(II), Cd(II), and Cr(III) ions can be obtained with different adsorbents at pH 4 [48, 51, 52].…”
Section: Methodsmentioning
confidence: 99%
“…It is non-biodegradable in environment and can accumulate in living tissues particularly in human bodies causing significant physiological disorders. Lead causes various detrimental biological effects including inhibition of the synthesis of hemoglobin and dysfunction in the kidney, reproduction system, liver, and central and peripheral nervous systems [1]. Lead ions are taken into human body via inhalation, ingestion and skin adsorption.…”
Section: Introductionmentioning
confidence: 99%